Pathogenic Variant in ACTB, p.Arg183Trp, Causes Juvenile-Onset Dystonia, Hearing Loss, and Developmental Delay without Midline Malformation - Erin Conboy; Filippo Vairo; Darrel Waggoner; Carole Ober; Soma Das; Radhika Dhamija; Eric W. Klee; Pavel Pichurin (Case Reports in Genetics)
ACTB encodes the β-actin, and pathogenic variations in this gene have typically been associated with Baraitser-Winter cerebrofrontofacial syndrome, a congenital malformation syndrome characterized by short stature, craniofacial anomalies, and cerebral anomalies. Here, we describe the third case with the p.Arg183Trp variant in ACTB causing juvenile-onset dystonia. Our patient has severe, intractable dystonia, developmental delay, and sensorineural hearing loss, besides hyperintensities in the caudate nuclei and putamen on the brain MRI, which is a distinct but overlapping phenotype with the previously reported case of identical twins with the same alteration in ACTB.